First comparison of LES of an offshore wind turbine wake with dual-Doppler lidar measurements in a German offshore wind farm. (June 2015) - Vollmer, L; van Dooren, M; Trabucchi, D; Schneemann, J; Steinfeld, G; Witha, B; Trujillo, J; Kühn, M
Abstract: Large-Eddy Simulations (LES) are more and more used for simulating wind turbine wakes as they resolve the atmospheric as well as the wake turbulence. Considering the expenses and sparsity of offshore measurements, LES can provide valuable insights into the flow field in offshore wind farms. However, for an application of LES wind fields to assess offshore wind farm flow, a proper validation with measured data is necessary. Such a proper validation requires that the LES can closely reproduce the atmospheric conditions during the measurement. For this purpose, a representation of the large-scale features that drive the wind flow is required. Large-scale-forcing and nudging of the LES model PALM is tested with reanalysis data of the COSMO-DE model for a case study during one particular day in the beginning of 2014 at a German offshore wind farm. As wind and temperature profiles of the LES prove to follow the large-scale features closely, the wake of a single wind turbine is simulated with an advanced version of an actuator disc model. Measurement data is provided by processed dual-Doppler lidar measurements during the same day in the same wind farm. Several methods have been investigated at the University of Oldenburg to compare LES wind fields and lidar measurements. In this study a dual-Doppler algorithm was applied in order to estimate the horizontal stationary wind field. The raw data originate from Plan Position Indicator (PPI) measurements, which have been performed with two long-range wind lidars installed at different opposing platforms at the border of the wind farm.